Fabrication of porous (Ba, Sr)(Co, Fe)O3-δ (BSCF) ceramics using gelatinization and retrogradation phenomena of starch as pore-forming agent. Issue 9 (15th June 2020) - Ishii, Kento; Shimizu, Makoto; Sameshima, Haruki; Samitsu, Sadaki; Ishigaki, Takamasa; Uchikoshi, Tetsuo
Abstract: Porous (Ba, Sr)(Co, Fe)O3-δ (BSCF) ceramics with high open porosity and good electrical conductivity was fabricated using Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF), which shows a high mixed ionic-electronic conductivity. In general, during the fabrication of porous ceramics by the sacrificial template method using pore former particles, closed pores are easily formed unless sufficient pore former particles are added. In this study, we have devised a method using the gelatinization-retrogradation phenomena of starch for producing a porous body with an excellent percolated pore network structure. By dispersing BSCF and starch in an aqueous slurry (0–50% by weight) and heating, gelatinization of the starch occurred and the starch particles adhered to each other. Furthermore, in order to retain the percolated structure, the water solvent was removed by freeze-drying without heating to obtain a dried green body. The sintering behavior of the porous BSCF bodies prepared under various conditions was characterized by microstructural observations and relative density measurements. By optimizing the process conditions of the gelatinization and retrogradation, a porous body having an open porosity of 48.3%, and with 99% of the total pores open, was obtained. The matrix was also well connected and showed a sufficiently high conductivity which was similar to the porous bodies made by the traditional sacrificial template method.